Ajuga taiwanensis Extract Promotes Wound-healing via Activation of PDGFR/MAPK Pathway - Hsu, Wei-Hsiang; Cheng, Jing-Jy; Wu, Ching-Fen; Lin, Yun-Lian (Planta Medica, 2024)
Chronic and prolonged wounds are a serious public problem that may severely affect the quality of life and result in psychological pressure. Fibroblasts play a crucial role in the wound process and in skin pathology. Herbal drugs have long been used for wound care worldwide. Ajuga taiwanensis (Lamiaceae) is a folk medicine for antipyretics, anti-inflammation, and reducing swelling in Taiwan. This study aimed to investigate the effect of A. taiwanensis in wound healing and the underlying mechanisms. Under human dermal fibroblast (HDF) wound-healing activity-guided fractionation, we found that a sub-fraction (AT-M) of A. taiwanensis extract (AT) and the major ingredients significantly promoted wound healing and decreased IL-1β and − 6 expressions on HDFs. Furthermore, the fraction of AT-M enhanced wound healing on C57BL/6 mouse skins, increased PDGFR expressions, and activated the PDGFR/MAPK pathway. Taken together, A. taiwanensis extracts promote wound healing by the PDGFR pathway and lead to enhanced cell spreading and motility, thereby having a possible beneficial effect on wound healing.
Keywords: Ajuga taiwanensis; Lamiaceae; human dermal fibroblasts; wound healing; PDGF receptor